Virulensi Cendawan Entomopatogen Beauveria bassiana terhadap Spodoptera litura (Lepidoptera: Noctuidae) Setelah Dipaparkan dengan Sinar Ultra Violet: english - Trizelia, Trizelia; Nurbailis, Nurbailis; Tanca, Cherly Yugu (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2018)
Beauveria bassiana is one of the entomopathogenic fungi to control various kinds of insect pests. Virulence of B. bassiana against insects could be affected by ultraviolet (UV) light. The study was aimed to determine the effect of different times of UV light exposure to B. bassiana against Spodoptera litura. The study was arranged in a Completely Randomized Design (CRD) with six different times of UV light exposure (control, 0, 15, 30, 45, 60 minutes) in four replications, respectively. Those B. bassiana were inoculated on the second instar of larvae of S. litura. The parameters observed were colony growth of B. bassiana, conidial germination, larval mortality, percentage of pupae, and adults formed. The data were analyzed by analysis of variance and LSD test at the 5% significance level. The results showed that exposure of B. bassiana to UV light reduced its germination but not inhibit the growth of B.bassiana. The exposure for 45 minutes and 60 minutes increased the virulence of B. bassiana that indicated by an increase of S.litura mortality (15.0-62.5%) and shorter LT50 (6.29-10.92).